REVIEW ARTIKEL : PERBANDINGAN HASIL EDIBLE COATING BERBASIS KITOSAN, PEKTIN, PATI, DAN KARAGENANTERHADAP MUTU DAN LAMA PENYIMPANAN BUAH TOMAT (Solanum lycopersicum L.) - La Asrafil; Daniel Daniel (PROSIDING SEMINAR KIMIA, 2023)
Tomato (Solanum lycopersicum L.) is a fruit-shaped vegetable that has the characteristics of being easily damaged. Tomato plants before, during and after harvest can be damaged quickly if the handling is not done properly, resulting in a decrease in quality. It is necessary to improve the quality and storage time of tomatoes, by using one type of coating, namely edible coating which has a function to improve the quality and storage time of tomatoes. Edible coating is a type of thin layer that is environmentally friendly and safe for consumption, which functions to maintain the quality of tomatoes from decay for a certain time. The study was conducted on edible coating research based on chitosan, pectin, starch, and carrageenan. The purpose of this article review is to compare the results of edible coatings from chitosan, pectin, starch, and carrageenan on the quality and storage time of tomatoes. The method used is the literature review method. The results showed that edible coating from cassava starch where tomatoes coated with edible coating with starch made from cassava was able to maintain the quality of tomatoes when stored until the 15th day. Chitosan showed chitosan coating with a concentration of 50 ppm was the best level for storage of tomatoes for 7 days of observation. Grapefruit peel pectin showed the best treatment was found in 3% pectin which was effective for 14 days with a weight of 0.063%. Carrageenan shows that 1.5% carrageenan edible coating stored at room temperature can extend the shelf life of tomatoes from 6 days to 10 days. Keywords: edible coating, carrageenan, chitosan, starch, pectin, tomato